Intervento di prevenzione, nel comparto trasporto e movimentazione merci, ASL 10 Firenze zona Nordovest / An injuries prevention programme in the transport and cargo handling sector, implemented by the ASL 10 Local Health Unit, Florence - Ariani, F.; Tomassini, A. (La Medicina del Lavoro, 2009)
Vi sono dubbi circa la capacità della UF PISLL di ridurre significativamente gli infortuni occupazionali tramite azioni di vigilanza ed indagine non mirate. Ciò ha condotto a progettare un intervento, rivolto alle attività di trasporto e movimentazione merci, che prevede di concentrare le azioni sulla minoranza di aziende a rischio più elevato e verificare ex-post i risultati ottenuti. Il tentativo di individuare le realtà più rischiose attraverso i dati infortunistici appare riuscito nelle aziende con oltre 3 addetti del comparto INAIL “18-Trasporti”. Permangono problemi per le piccolissime aziende e per le cooperative di facchinaggio, per le quali i dati sul numero di addetti risultano poco affidabili.An injuries prevention programme in the transport and cargo handling sector, implemented by the ASL 10 Local Health Unit, FlorenceBackground: There are doubts about the ability of public health services to significantly reduce occupational injuries through non-targeted investigations and surveillance programmes. Methods: For this reason an intervention was designed specifically for the transport and cargo handling sector, in which inspections are concentrated on the minority of higher risk companies, followed by ex-post assessment of the outcomes. Results and discussion: The goal of identifying the most hazardous companies through injury data appears to be successful in companies with more than 3 employees. Some problems remain for smaller companies and for the large porterage cooperatives, where the official data on the number of employees is unreliable.